Identifikacija nadarenosti u nastavnom procesu predmeta likovna kultura / Giftedness Identification in Teaching Process of Visual Art - Vrbić-Mačak, Biljana (Pregled: časopis za društvena pitanja / Periodical for social issues, 2018)
Crucial aim of elementary education is to form a creative, self – confident personality neccessary for the advance of a society. A good quality teaching process can only be realised in an incouraging atmosphere and a good interactive relationship among all the participants. Classes are organized for a group of students according to their age with a stress on the individualization, which is of a vital importance for a harmonized development of each child. For that reason more attention should be paid to better preparing teaching staff so that teaching process, raising and education become largely pedagogical relationship in recognizing and building students' personality. Both teachers and parents should professionally be introduced with the idea of what giftedness is and how it is expressed and recognized. This paper deals with a complex range of issues of giftedness and how this phenomenon should be lightened up in all its segments. Special attention was paid to a specific giftedness – visual art giftedness. Visual art classes have good conditions for differentiation and individual approach to each student, thus giving the opportunity, quite easily, to each one, including the talented ones, in the best suitable way to influence the most important aim of education: the development of a free, independent personality.